2018
DOI: 10.1016/j.physletb.2018.08.060
|View full text |Cite
|
Sign up to set email alerts
|

Safe jet vetoes

Abstract: Central jet vetoes are powerful tools for reducing QCD background in measurements and searches for electroweak and colorless, new physics processes in hadron collisions. In this letter, we report the key findings of a new philosophy to designing searches for such phenomena at hadron colliders, one designed and centered around a dynamical jet veto instead a static veto applied independently of other selection criteria. Specifically, we investigate the theoretical and phenomenological consequences of setting the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 84 publications
4
56
0
Order By: Relevance
“…This is not necessarily the case for the W +jets background, therefore requiring that E miss T < p µ T will help reducing it. Indeed, and more generally, what we will want to do is to look for events in which the leading particle is a muon, in a similar way to the dynamical jet veto proposed in [33].…”
Section: Signal Characterization and Search Strategiesmentioning
confidence: 99%
“…This is not necessarily the case for the W +jets background, therefore requiring that E miss T < p µ T will help reducing it. Indeed, and more generally, what we will want to do is to look for events in which the leading particle is a muon, in a similar way to the dynamical jet veto proposed in [33].…”
Section: Signal Characterization and Search Strategiesmentioning
confidence: 99%
“…Among the several promising lines of such investigations are those that consider the impact of jet vetoes (i.e., the rejection of events featuring jets with a transverse momentum greater than some threshold p Veto T [15- * Electronic address: fuks@lpthe.jussieu.fr † Electronic address: knordstrom@lpthe.jussieu.fr ‡ Electronic address: richard.ruiz@uclouvain.be § Electronic address: sophie.williamson@kit.edu 19]) in measurements of and searches for heavy, colorless SM [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and beyond the SM [35][36][37][38][39][40][41][42] states. Interestingly, recent studies of multilepton searches for heavy, colorless exotic particles have demonstrated that dynamic jet vetoes can significantly improve discovery potential [41,42]. More specifically, a proposed analysis premised on setting p Veto T on an event-by-event basis to the hardness (p T ) of the event's leading lepton was found to improve sensitivity by roughly an order of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, we see that typical [102] experimental jet veto thresholds of p Veto T = 20 − 40 GeV, reduce triplet production cross sections severely and potentially discourage their use. However, we note that the criteria needed to employ a socalled dynamic (or event-based) jet veto [47][48][49], which can significantly improve jet veto efficiencies and background rejection rates, appear to be satisfied. Investigations into dynamic jet vetoes in triplet scalar searches is left to future work.…”
Section: Iv11 Triplet Scalar Production With Jet Vetoes At Nlo+nnllmentioning
confidence: 95%
“…Following signifiant improvements in modeling soft jet activity in both color-singlet and QCD processes, the use of jet vetoes in direct searches for new phenomena is becoming increasingly standard at the LHC, as shown, for example, in Refs. [47][48][49][95][96][97]. With the TypeI-ISeesaw libraries it is possible to predict jet veto cross sections for triplet scalars up to NLO+NNLL(veto) using the MadGraph5 aMC@NLO-SCET formalism of Refs.…”
Section: Iv11 Triplet Scalar Production With Jet Vetoes At Nlo+nnllmentioning
confidence: 99%
See 1 more Smart Citation